Investigation of nitrogen dioxide behavior in Mashhad and its relationship with Meteorological Parameters - Atefeh Shahmohammadi; Ali Bayat; Saeed Mashhadizadeh Maleki (تحقیقات کاربردی علوم جغرافیایی)
Urban development and air pollution are among the most important issues related to climate. The expansion of urbanization and urban development, population growth, industrial development and excessive use of fossil fuels significantly increased air pollution and it is more than the capacity of the environment. In our country, the emissions of air pollutants in some metropolitan areas have reached a dangerous level, Mashhad is considered to be the most polluted cities of the country in some days of the year. Nitrogen dioxide is one of the indicators of air pollution. In this study, the OMI data and atmospheric parameters such as wind, surface temperature, and horizontal visibility data for the period from 2004 to May 2016 were used to investigate the air pollution in Mashhad. The results show that the maximum (minimum) nitrogen dioxide levels occur in the cold (hot) season. The highest amount of nitrogen dioxide in January is equal to 5.56 × 1015  molec/cm2 and its lowest value in September is 4.18 × 1015  molec/cm2. Standard deviation of nitrogen dioxide also indicates that the greatest changes occur in cold seasons. Also, the results showed that the dominant wind in the city of Mashhad is from the south, and most of the winds are slow. Correlation coefficient of nitrogen dioxide with wind and surface temperature is -0.36 and -0.57, respectively, which shows the higher importance of temperature in nitrogen dioxide changes in Mashhad city. The correlation coefficient of nitrogen dioxide with horizontal visibility is -0.15, which indicates that with increasing nitrogen dioxide contamination, horizontal visibility decreases. Spectral analysis of least squares of the six and twelve-month periods of rotation was observed, they were also statistically significant. After eliminating the significant components of the time series of the average monthly nitrogen dioxide, the trend was calculated. The amount of nitrogen dioxide in each year for Mashhad was 2.41 × 1013  molec/cm2.